Transfer learning models for bacterial strain dissemination biomarkers using weighted non-parallel proximal support vector machines - Ugwu, Ugochukwu O; Slayden, Richard A; Kirby, Michael (Tufts University Tisch Library, 2026)
Keywords: Data Integration, Dimensionality Reduction, Gene Selection, Machine Learning, Optimization, Pathway Analysis, Support Vector Machine; Springer Open.